The Effectiveness of a Counseling Cognitive- Behavioral Program in Improving Psychological Well- Being among Al- Quds Open University Students - Muhannad Yasser Saleh Dameri; Hussni Muhammad Awad (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: This study aims to reveal the effectiveness of a counseling cognitive behavioral program in improving the psychological well-being among Al- Quds Open University Students.  Methods: The researcher used the semi-experimental approach. The study sample comprised (30) university students (males/females) who have low degree of psychological well-being. The study sample was divided into two groups, experimental and control groups. The researcher applied for the counseling program to the experimental group, while the control group did not receive any kind of counseling. The counseling program included (15) sessions, with two sessions per week, and the duration of each session has lasted for (90) minutes.  Results: The study showed the mean scores of psychological well-being according to the post-measurement in favor of the experimental group with a (0.922) value. The differences were also significant in the experimental group concerning the pre and post-measurement in favor of the post-measurement. The results indicated the effectiveness of the counseling program in improving psychological well- being among university students and the effectiveness of the counseling program.  Conclusions: The study recommends the need to invest in the cognitive-behavioral counseling program used in the current study on other groups in society and evaluate its effectiveness with each category of society. Additionally, it recmmends taking care of the preparation of counseling programs in universities to deal with problems and mental disorders that lead to a decrease psychological well-being among university students.